2015
DOI: 10.1021/acscatal.5b00898
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Pd0-Catalyzed Asymmetric Activation of Primary and Secondary C–H Bonds Enabled by Modular Binepine Ligands and Carbonate Bases

Abstract: International audienceNew binepine ligands have been synthesized, and characterized and have been shown to induce high diastereo- and enantioselectivity in the intramolecular arylation of primary and secondary C(sp3)–H bonds, giving rise to fused cyclopentanes. The ligands were obtained as bench-stable phosphonium tetrafluoroborate salts that can be directly employed in catalysis. It was shown that a ferrocenyl P-substituent on the ligand allows achievement of high stereoselectivities in combination with potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(49 citation statements)
references
References 68 publications
0
48
0
1
Order By: Relevance
“…[184] Fort he synthesis of enantiomerically enriched dihydroindene 463 from vinyl bromide 462,C lot, Baudoin, and co-workers utilized axially chiral phosphine LG13 (Scheme 87). [185] TheY uresearch group demonstrated an enantioselective palladium-catalyzed carbonyl-directed C(sp 3 )ÀHa ctivation. Thedifferentiation of the two pro-stereogenic methyl groups can be accomplished, albeit with moderate stereoselectivity in most cases,byusing amodified amino acid as achiral ligand on palladium (Scheme 88).…”
Section: Transition-metal-catalyzed Càha Ctivationmentioning
confidence: 99%
“…[184] Fort he synthesis of enantiomerically enriched dihydroindene 463 from vinyl bromide 462,C lot, Baudoin, and co-workers utilized axially chiral phosphine LG13 (Scheme 87). [185] TheY uresearch group demonstrated an enantioselective palladium-catalyzed carbonyl-directed C(sp 3 )ÀHa ctivation. Thedifferentiation of the two pro-stereogenic methyl groups can be accomplished, albeit with moderate stereoselectivity in most cases,byusing amodified amino acid as achiral ligand on palladium (Scheme 88).…”
Section: Transition-metal-catalyzed Càha Ctivationmentioning
confidence: 99%
“…3,4 The C–H cleavage step in these reactions is most commonly proposed to proceed via a base-promoted concerted metalation–deprotonation (CMD) mechanism. 5 Although other C–H bond metalation pathways, such as oxidative addition (OA), 6 σ-complex-assisted metathesis (σ-CAM), 7 and ligand-to-ligand hydrogen transfer, 8 are well precedented in the literature, these alternative mechanisms have not been thoroughly investigated in C–H functionalization reactions involving N , N -bidentate directing groups. 9 Because previous computational mechanistic studies of this type of reactions all focused on the CMD mechanism, 10,11 it is not clear what conditions would promote an alternative C–H bond cleavage pathway.…”
Section: Introductionmentioning
confidence: 99%
“…. Copyright 2016, John Wiley and Sons.These intramolecular cyclisations have been extended to the diastereo-and enantioselective syntheses of indanols114 and indanes 110. With 52-Br (Figure 21, R = i Pr) reaction proceeds via the C-Br activated [Pd(52)(CO3 -)L] intermediate, where L is a chiral binepine-based phosphine ligand and carbonate is again sited trans to the vacant site.…”
mentioning
confidence: 99%